Design Of Transceiver For UWB Applications - Sit, Yoke Leen (Universiti Sains Malaysia, 2006)
An RF front-end Direct Conversion (DICON) transceiver architecture for Mode 1 multiband Orthogonal Frequency Division Multiplexing (OFDM) applications is presented in this dissertation. This effort on building a prototype is to serve as a reference model for workability to be transferred onto a single chip system using The RF front-end transceiver is designed on system level using Agilent’s Advanced Design System (ADS) and the prototype was built on the FR4 type printed circuit board (PCB) employing passive networks such as power-splitter, low-pass and band-pass filters as well as quadrature phase shifters, for better integration with other devices on PCB. The major operations blocks such as the I&Q Modulator, I&Q Demodulator and the Voltage Controlled Oscillator (VCO) employed are microwave-based components from Mini-Circuits while the Low-Noise Amplifier (LNA) and Power Amplifier (PA) employed are p-type High Electron Mobility Trasnsistor (pHEMT) based, from Agilent Technologies. The transceiver prototype is complete with microstrip rectangular patch antennas which have a bandwidth of 17MHz and a 3dB beamwidth of 80° for wireless transmission. The band-pass filter and the low-pass filter have been designed with third order response possessing a bandwidth of 423MHz and 260MHz respectively. The transceiver system has an operational bandwidth of up to 200MHz but its bandwidth is severely limited by the rectangular patch antenna, thus allowing only a 17MHz operational bandwidth. Since high-frequency devices are not commercially available, the operational frequency of the transceiver system has to be scaled down to a carrier frequency (LO) of 1.60GHz from the intended 3.96GHz. Also, the test baseband signal has been set to 80MHz to accommodate bandwidth restrictions of the overall system. The prototype was tested separately as a transmitter and a receiver to ease the testing and troubleshooting procedure. The prototype was tested to have a stability of operation of up to 2.5m. The average transmit power is -36dBm without utilizing a PA while the receiver sensitivity is around -65dBm. The recovered baseband signal consists of the I and Q signals which were found to be at the frequency test baseband signal of 80MHz, with a maximum power of -22dBm. The I and Q signal exhibit a 20% mismatch in amplitude but otherwise is at quadrature phase apart.